Cosmic clouds : birth, death, and recycling in the galaxy - Kaler, James B. (New York : Distributed by W.H. Freeman, 1997)
Studies the clouds of interstellar space, considering the process by which new stars are formed, looking at how star birth generates planets and perhaps life, and studying how the deaths of stars begins the process anew.
Includes bibliographical references (p. 243) and index.
Choice.
Young Adult
Keywords: Astrophysics; Galaxies; Stars; Astrophysics; Galaxies; Stars